Aberrant Expression of JAM2 Inhibits Invasion and Migration in Lung Adenocarcinoma - Jun Chen; Yuan Cui; Zhimeng Chen; Hao Ding; Chang Li; Sheng Ju; Cheng Ding; Chun Xu; Jun Zhao; Xin Tong (Cancer Reports)
ABSTRACT Background Lung adenocarcinoma (LUAD) is the most common histological subtype of lung cancer. JAM2, a member of the Junctional adhesion molecule (JAM) family, plays diverse roles in cell–cell contacts and tumor development. Although JAM2's expression and functions have been reported in various cancers, its clinical and biological significance in LUAD remains unclear. Aims The aim of this study was to investigate the expression and function of JAM2 in LUAD, and to assess its potential as a prognostic gene and a molecular target for early diagnosis and targeted therapy. Materials Immunohistochemistry (IHC) was performed on 37 pairs of LUAD tissues. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were conducted among co‐expression genes in different JAM2 subgroups. In vitro experiments were also conducted to study the migratory and invasive capabilities of LUAD cells when JAM2 was overexpressed. Results The study confirmed that JAM2 was downregulated in LUAD, possibly due to methylation. JAM2 emerged as an independent prognostic gene for predicting the outcomes of patients with LUAD. IHC analysis revealed the significance of JAM2 with clinicopathological parameters in LUAD. GO and KEGG analyses provided insights into the biological processes and pathways associated with JAM2. In vitro experiments showed that overexpressing JAM2 significantly suppressed the migratory and invasive capabilities of LUAD cells. Additionally, JAM2 played a crucial role in LUAD inflammatory infiltration, and higher JAM2 expression predicted a better immunotherapy response. Conclusion JAM2 may serve as a promising molecular target for early diagnosis and targeted therapy of LUAD. Its downregulation in LUAD, potential role as a prognostic gene, and influence on cell migration, invasion, and inflammatory infiltration make it a valuable target for further research and development of therapeutic strategies.